International opportunity recognition and export satisfaction in SMEs through export intermediary networking - Ahmadian, Sahar (2012)
International Opportunities Recognition (IOR) is the heart of International Entrepreneurship (IE) literature and has been found to be the main success factor in IE studies. Despite its importance, IOR is also the major barrier for the internationalization of SMEs. Prior studies on IOR have focused on the role of individuals and characteristics of firms and found that SMEs suffered from individual’s cognitive limitation and firm’s insufficient resources. However, little is known about the methods adopted by entrepreneurs to compensate the individual’s cognitive and firm’s resource limitation for opportunity recognition. This study approached the problem by adopting a Network Based View (NBV) derived from IE literature and applied the network to IOR. The purpose of this study is to explore the significant role of Export Intermediaries Networking (EIN) in finding opportunities in international markets and achieving export satisfaction for SMEs based on the limitation of individual cognitive and firm’s resources. NBV was used to examine the mediating effect of IOR on the relationship between EIN with export satisfaction. Besides that, the study attempted to determine the relationship between IOR and export satisfaction. A quantitative method using simple random sampling was employed. A cross-sectional was utilized using structured questionnaire from which 265 responses out of 500 managers of SMEs manufacturer in Malaysia responded to the questionnaire. Multiple regression, bivariate correlation, and path analysis were employed to test the relationship between variables. Findings revealed that EIN had positive significant correlation with IOR and export satisfaction. In addition, this study found a positive significant correlation between IOR and export satisfaction. Beside that, IOR mediated the relationship between EIN and export satisfaction. Results for marketing capabilities, experience assets, and relation assets significantly clarify regression showed a 67 per cent of the variance in IOR. Likewise, these variables also had 57 per cent of the variance in the export satisfaction. The findings of this study have contributed towards the IE literature as well as provide a new perspective of managerial application for export managers to move beyond their individual cognitive and firm’s resources limitations by networking with export intermediaries.